New bench for testing the reliability of windows and doors of passenger cars - V. A. Makarov (Вестник Научно-исследовательского института железнодорожного транспорта)
The article describes a new bench for testing the reliability of passenger car windows and doors. The bench can be used in various industries, mainly in transport engineering, as well as in the construction industry. This bench is functionally designed to test the entire product (windows or doors), as well as to determine the service life of individual mechanisms of this product. In contrast to the known analogs, the new bench for testing the reliability of windows and doors allows testing under the influence of variable aerodynamic pressure arising from the operation of windows and doors on moving objects, for example on high-speed transport. Specially developed test method is proposed on this bench, which allows simulating alternating aerodynamic effects on windows and doors that occur when a train passes tunnels or when trains in opposite directions diverge at high speeds. Thanks to this, bench tests can serve as an actual addition to the existing methods of testing windows and doors of modern high-speed rolling stock.